Efikasi Ekstrak Daun Pepaya Terhadap Nezara viridula L. (Hemiptera : Pentatomidae) Pada Polong Kacang Panjang - Jeffie V Hasinu; Ria Y Rumthe; R Laisow (Agrologia, 2014)
Nezara viridula is one of the major pests which attack  bean (Vigna sinensis) plants. Crop damage due to  attack of N. viridula depend on the number of pests, the availability of nutrition as well as  biotic and abiotic factors. The useof synthetic insecticides continuously with inappropriate dose and time application cause negative impact on the environment, therefore the use of insecticide plant is one alternative to reduce pesticide dose. The purpose of this study was to determine the concentration of papaya leaf extract and verify application method which promote  mortality of N. viridula ninfa. Experiment was set up in completely randomized block design with four treatments, i.e 40 g/100 mL of water, 50 g/100 mL of water, 60 g/100 mL of water and 70 g/100 mL of water. Observations were made on early symptoms of toxocity, the percentage of mortality, mortality rate and advanced stages of N. viridula. The results showed that application of papaya leaf extract with at 70 g / 100 mL of water through feed or contact caused 100%  mortality of N. Viridula,  with  mortality rate of 4.75 days and 5.50 days. It is sugeested that  vegetable-based insecticide could be used to decrease N. viridula attack on string bean pod.